Electrochemical Studies Of N'-ferrocenylmethyl-n'-phenylbenzohydrazide At Glassy Carbon Electrode In Different Medium - Khelef, A.; Neghmouche, N. S.; Lanez, T. (University of Eloued جامعة الوادي, 2011)
The oxidative electrochemistry of N'-Ferrocenylmethyl-N'-Phenylbenzohydrazide FcX was studied in acetonitrile with tetrabutylammonium hexafluorophosphate as the supporting electrolyte and aqueous ethanol using the electrochemical technique. This study using cyclic (CV) and rotating disk electrode (RDE) voltammetry showed that the FcX/FcX+ redox couple is reversible in this electrolytes. The effects of changing the scan rate on the electrochemical behavior of ferrocene have been examined. A comparison of the electrochemical behavior of ferrocene and N'-Ferrocenylmethyl-N'-Phenylbenzohydrazid have been examined.
Articale in Journal of fundamental and Applied Sciences Vol. 03 N. 02
Keywords: Cyclic voltammetry, ferrocene, N'-Ferrocenylmethyl-N'-Phenylbenzo-hydrazid, half-wave potential.